The usefulness of reading techniques in the development of reading comprehension proficiency of students from Readings and Conversation I course at the Department of Foreign Languages of the University of el Salvador during the year 2015. - Pineda Delgadillo, Camila; Recinos Hernández, Jessica Beatriz; Villatoro Hernández, Karen Guadalupe (2024)
Over the last decades, English has become widely regarded as a global language, as David Crystal has commented, “one in four of the world’s population is now capable of communicating to a useful level in English” (Crystal, 1997, p69). In fact, based on native speakers, it is considered the third most spoken language in the world according to the latest editions of The Encyclopaedia Britannica yearbook, and Ethnologue: languages of the world (2014) .But it remains in the first place as the most learned language with 1,500 million English learners. Due to this importance of English in our globalized world, the University of El Salvador created the Department of Foreign Languages in 1956 including the English Teaching Language major in 1977 (Modified in 1999) and the Modern Languages major in 20021. One of the main purposes of the students for these majors is to have a complete knowledge of the four language skills, which are the following: listening, speaking, writing and reading. The present work will be focused on the last skill mentioned and its development on reading comprehension by using the basic reading techniques learned during the Readings and Conversation I course. It is important to remark that even though reading is simply defined as the act of reading3. Reading comprehension is a complex process. The process through which the interaction of the reader’s background knowledge, the information inferred by the written language, and the reading situation context is constructing meaning from text (Dutcher, 1990).